Engaging with AI painting: exploring motivations and challenges in laypeople's creative information practices - Xiaoyu Zhang; Sicheng Zhu; Yuxiang Chris Zhao; Mingxia Jia; Qinghua Zhu (Information Research: An International Electronic Journal)
Introduction. The advent of generative AI has democratized art creation, enabling individuals without formal training to produce visually appealing digital artworks. However, it is not yet well-understood why and how laypeople engage with AI in creative information practice.